Complications of image-guided liver biopsies: Results of a nationwide database analysis - Markus Graf; Christiana Graf; Sebastian Ziegelmayer; Alexander W. Marka; Marcus Makowski; Yannick Teumer; Philipp Paprottka; Nele Willemsen; Jonathan Nadjiri (PLoS ONE, 2025)
Background and aims Liver biopsy is the gold standard for evaluating liver diseases, the diagnosis of liver fibrosis or liver cirrhosis and malignancy. However, it is susceptible to complications, and safety data on liver biopsies remain scarce. The following study examined the complication rates following percutaneous liver biopsies. Methods We performed a study using data collected by the German interventional radiology society (DeGIR) from 2018 to 2021 of elective percutaneous liver biopsies. Clinical and hematological parameters, technical features and adverse events were retrospectively examined. Results From 2018 to 2021, a total of 12117 percutaneous liver biopsies were performed in 194 participating centers in Germany. Complications occurred in 235 biopsies (1.9%), of which 195 (1.6%) were major adverse events. Minor complications in the form of procedural hypotension and pain occurred in 7 and 33 cases (0.06% and 0.3%, respectively). Major complications such as bleeding, organ injury and pneumothorax were observed in 166, 3 and 26 cases (1.4%, 0.02% and 0.2%). Three subjects (0.02%) died as a result of massive intraperitoneal bleeding. Major and bleeding complications were significantly more frequently observed in patients with thrombocytopenia (p < 0.001) as well as in patients undergoing computed tomography (CT)-guided procedure compared to ultrasound-guided one (p < 0.001). Moreover, general and bleeding complication rates significantly differed by the liver segment biopsied (p < 0.001). In contrast, the type of needle size used (p = 0.323), internationalized ratio (INR) (p = 0.09), aPTT (p = 0.98), gender (p = 0.83), age (p = 0.08) and the number of biopsies (p = 0.91) performed did not impact the frequency of major adverse events. By multivariate logistic regression analysis, platelet count, the imaging modality used (CT vs. ultrasound-guided) and the liver segment biopsied were identified as independent risk factors of post-biopsy bleeding (p < 0.001 each). Conclusion Percutaneous liver biopsies are safe with rare procedural morbidity. Our data confirm previous data by showing that post-procedural bleeding was not associated with INR and aPTT in patients undergoing invasive procedures. However, measurement of platelet count is indicated to identify patients with increased procedural bleeding risk. Moreover, our findings suggest that patients with liver cirrhosis as well as patients with complex findings and difficult localizations could benefit from intensified monitoring post-procedural.